Pengaruh Perputaran Kas, Perputaran Piutang, dan Pertumbuhan Jumlah Nasabah Kredit terhadap Return on Assets pada Lembaga Perkreditan Desa - Methy Dharmayanti Suanda; Gede Putu Agus Jana Susila (Jurnal Akuntansi Profesi, 2022)
This study aims to examine the effect of cash turnover, accounts receivable turnover, growth in the number of credit customers on return on assets (ROA) either partially or simultaneously. The population used in this study is the LPD in Tejakula Subdistrict, amounting to 15 LPD. This research uses quantitative methods. Data collection techniques in this study are using document recording. Next, the data were analyzed using multiple linear regression analysis. The results showed that there was a significant influence of cash turnover, accounts receivable turnover and growth in the number of credit customers on ROA both partially and simultaneously. This study also shows that the contribution of cash turnover, accounts receivable turnover, and growth in the number of credit customers to ROA of 98.2%, the remaining 1.8% is explained by other variables outside this study.